LEGAL MECHANISMS FOR THE FORMATION OF MODERN GENDER POLICY (Вісник: Міжнародні відносини, 2025)
Globalization transformations have created new forms of inequality and discrimination, with women disproportionately affected by economic globalization in the global division of labor. Gender plays an important role in the way labor is organized and is a central organizing principle of the global economy. The purpose of the study is to investigate the nature of gender inequality in contemporary international relations. To analyze the formation of an appropriate legal mechanism and identify effective strategies to reduce the gender gap in the world.